Effect of Prosopis juliflora thorns on mechanical properties of plastic waste reinforced epoxy composites - Ganapathy, Sakthi Balan; Sakthivel, Aravind Raj; Hameed Sultan, Mohamed Thariq; Shahar, Farah Syazwani; Md Shah, Ain Umaira; Khan, Tabrej; Sebaey, Tamer A. (MDPI, 2022)
Plastics are unavoidable at this times, putting our planet in danger. The Prosopis juliflora (PJ) thorns are collected, processed, and powdered. The mechanical characteristics of these powders are examined when combined with polymer composites. Pores are the main cause of moisture input, hence using powder filler materials reduces the number of pores in the composite, increasing water resistance. The composites are made by altering three parameters: waste plastic content, filler powder composition, and chemical treatment. It was discovered that the integration of thorn powder increased the wear resistance. The composites were tested in accordance with ASTM standards, and the results were optimized. Based on the results, composite specimens were created and tested for validation.